2017
DOI: 10.1111/jog.13444
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod against endotoxin‐induced fetal brain injury in a rat model

Abstract: Antenatal maternal fingolimod therapy had fetal neuroprotective effects by alleviating preterm birth-related fetal brain injury with inhibitory effects on inflammation and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In non-obese diabetes EAE mice, FTY720 administration resulted in the decreased expression of reactive A1 astrocytic factors (including manganese-dependent superoxide dismutase (MnSOD), IL-6, CCL2, CXCL10, IL-1β, TNFα), and an upregulation of CXCL12 and IL-33 [65]. This effect of FTY720 on pro-inflammatory cytokines was confirmed in other rodent disease models [47,48,54,84,87,91]. Furthermore, the expression and secretion of pro-inflammatory cytokines in vitro was also reduced following treatment with FTY720 in both human and rodent primary cells from fetal and adult origin [65,73,[92][93][94] as well as in an astrocytoma cell line [95], while only one study has reported no effect of FTY720 on IL-1β and CCL2 [96].…”
Section: Astrocytesmentioning
confidence: 69%
See 1 more Smart Citation
“…In non-obese diabetes EAE mice, FTY720 administration resulted in the decreased expression of reactive A1 astrocytic factors (including manganese-dependent superoxide dismutase (MnSOD), IL-6, CCL2, CXCL10, IL-1β, TNFα), and an upregulation of CXCL12 and IL-33 [65]. This effect of FTY720 on pro-inflammatory cytokines was confirmed in other rodent disease models [47,48,54,84,87,91]. Furthermore, the expression and secretion of pro-inflammatory cytokines in vitro was also reduced following treatment with FTY720 in both human and rodent primary cells from fetal and adult origin [65,73,[92][93][94] as well as in an astrocytoma cell line [95], while only one study has reported no effect of FTY720 on IL-1β and CCL2 [96].…”
Section: Astrocytesmentioning
confidence: 69%
“…FTY720 reduced the number of cells positive for reactive A1 astrocytic markers glial fibrillary acidic protein (GFAP) and S100 calcium-binding protein B (S100β) in multiple rodent models, including in a model of familial AD [45,51], cuprizone-induced demyelination [48], MS [50,61,82], Huntington's disease (HD) [84], Status epilepticus (SE) [54], and models of infection [85], stroke [86], ICH [47], Pentylenetetrazol (PTZ)-induced kindling [56], and maternal inflammation [87] as well as wild-type rodents [88]. In contrast, FTY720-treated immortalized astrocytes displayed increased release of the astrocyte-secreted protein GM-CSF [89], whereas LPS-stimulated primary astrocytes decreased GM-CSF release following treatment with FTY720 [65].…”
Section: Astrocytesmentioning
confidence: 99%
“…All brain samples, SNpc sections, were analyzed semiquantitatively as follows. Five different sections were examined in each sample, which then were scored from 0 to 3, according to the intensity (0, absence of staining; 1, slight; 2, medium, and 3, marked) [30]. After the routine microscopic examination, computer-assisted histomorphometric measurements and immunohistochemical scoring were obtained using an automated image analysis system (Olympus CX41, Olympus Corporation, Tokyo, Japan).…”
Section: Histopathology and Immunohistochemistry Analysesmentioning
confidence: 99%